1987
DOI: 10.1042/bj2450929
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of sugars into rat liver lysosomes. Evidence against a common carrier for d-glucose and d-ribose

Abstract: A conflict exists in the literature concerning the mode of translocation of D-glucose and D-ribose across the lysosome membrane. The more rapid net uptake of ribose, when measured by the osmotic-protection technique, has been attributed either to its smaller size and lower hydrogen-bonding capacity, or to a lower affinity for a transport system shared by both sugars. The latency of acid beta-hexosaminidase in isolated rat liver lysosomes was measured after preincubation for periods up to 1 h in various solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…1, Table 1) that the behaviour of the mixture may or may not be intermediate between that of either sugar alone, depending on their Km values. The intermediate behaviour found in the experiments of Bird et al (1987) therefore cannot be used to argue for the absence of a lysosomal transport system for ribose and glucose.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…1, Table 1) that the behaviour of the mixture may or may not be intermediate between that of either sugar alone, depending on their Km values. The intermediate behaviour found in the experiments of Bird et al (1987) therefore cannot be used to argue for the absence of a lysosomal transport system for ribose and glucose.…”
mentioning
confidence: 87%
“…: a reply The main point at issue is not whether a monosaccharide transporter exists in the rat liver lysosome membrane, but the mechanism(s) by which sugars cross this membrane. In our recent paper (Bird et al, 1987) we quoted both the evidence for a glucose carrier (evidence repeated in the Letter by Maguire et al, 1988) and also the evidence that some sugars and their derivatives cross by passive diffusion. In their most recent experimental paper on sugar translocation across the lysosome membrane, Maguire et al (1983) concluded (we believe wisely) that glucose crosses partly by facilitated and partly by passive diffusion.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…The latency of a lysosomal enzyme refers to the percent of intact lysosomes as revealed by the inability of substrate to reach the lysosomal enzyme until the organelles are deliberately ruptured (Greene and Schneider, 1992). 4-Methylumbelliferyl Nacetyl-␤-d-glucosaminide, the substrate of lysosomal ␤-hexosaminidase, was used at 1 mM to measure the enzyme activity (Bird et al, 1987). The liberated 4-methylumbelliferone was determined by measuring its fluorescence (excitation 365 nm, emission 444 nm) on a Hitachi F-4010 fluorescence spectrophotometer.…”
Section: Assay Of Lysosomal Integritymentioning
confidence: 99%